Consent agreements for cryopreserved embryos: the case for choice. Issue 4 (25th March 2010) - Sozou, Peter D; Sheldon, Sally; Hartshorne, Geraldine M
Abstract : Under current UK law, an embryo cannot be transferred to a woman's uterus without the consent of both of its genetic parents, that is both of the people from whose gametes the embryo was created. This consent can be withdrawn at any time before the embryo transfer procedure. Withdrawal of consent by one genetic parent can result in the other genetic parent losing the opportunity to have their own genetic children. We argue that offering couples only one type of consent agreement, as happens at present, is too restrictive. An alternative form of agreement, in which one genetic parent agrees to forego the right to future withdrawal of consent, should be available alongside the current form of agreement. Giving couples such a choice will better enable them to store embryos under a consent agreement that is appropriate for their circumstances. Allowing such a choice, with robust procedures in place to ensure the validity of consent, is the best way to respect patient autonomy.